Ijtihad Tidak Membatalkan Ijtihad Yang Lain (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2018)
The results of an ijtihad are strongly influenced by the circumstances under which the law is formulated. This resulted in the process of ijtihad being carried out frequently resulting in varied formulas when the context of the problems arose differently. As a product of ijtihadi, the established law is not something sacred and closes the door of difference and change. The emergence of various results ijtihad difference is not apart from the process of formulating the law itself. The process of implementing ijtihad with its various rules is very instrumental in the results and the influence of the deciding law. Therefore, a Mujtahid must be able to comprehend the rules of ijtihad perfectly.